Perspektif Hukum Lingkungan Nasional dan Komitmen Internasional Indonesia di Sulawesi Tenggara - Anawai, Idha Gusti; Petilik , I Kadek Agus Salim; Wiyadi, Kahfi; Pinaya , Fitrah Ramadhan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The issue of deforestation and environmental damage in Southeast Sulawesi has become a strategic issue that impacts not only national environmental sustainability but also Indonesia's international commitments to global environmental protection. Uncontrolled exploitation of natural resources, weak law enforcement, and overlapping regulations have led to increasing forest degradation and ecosystem damage. This study aims to analyze the national environmental law perspective on environmental management in Southeast Sulawesi and examine the implementation of Indonesia's international commitments to combat deforestation and maintain environmental sustainability. The research method used is normative legal research with both legislative and conceptual approaches. The results show that although Indonesia has various environmental regulations and ratified several international legal instruments related to climate change and forest protection, their implementation remains suboptimal. Weak inter-agency coordination, ineffective oversight, and the dominance of economic interests are the main factors hindering environmental protection.